Preoperative clinical, subclinical characteristics and nutritional status of gastric cancer patients at Vietnam National Cancer Hospital - Dang, Nguyen Van; Luong, Nguyen Hong (Tạp chí Nghiên cứu Y học, 2024)
Gastric cancer ranked fourth for incidence and mortality of all cancers in Vietnam. Clinical symptoms in the early stages are often nonspecific. Patients may have epigastric pain, anorexia or weight loss. Gastroscopy combined with biopsy is a clinical test that helps diagnose gastric cancer. Endoscopic ultrasound, computed tomography of the abdomen and chest are important examinations to assess the stage of the disease. Gastric cancer patients had a high rate of malnutrition, and preoperative nutritional management represents a challenge. Cross-sectional descriptive research was conducted on 88 gastric cancer patients aged over 18 years old to describe preoperative clinical, subclinical characteristics and nutritional status at National Cancer Hospital from January to December 2023. Epigastric pain was the most common clinical symptom with 92%, ulceration type was the most common macroscopic type with 63.9%, poorly differentiated adenocarcinoma was the most common histopathological type with 43.2%, 53.4% of anemic patients. The preoperative malnutrition rate according to albumin, BMI and PG-SGA were 34.1%, 29.5% and 55.7% respectively. Research shows that some preoperative clinical and paraclinical characteristics were very typical of a gastric cancer patient. A very high rate of malnutrition was found in gastric patients before surgery.